Unilateral multicystic dysplastic kidney complicated with urinary tract infection by E. coli in a premature newborn - Gabriela-Maria Chifa; Laura-Mihaela Suciu; Cristina Oana Marginean (Romanian Journal of Pediatrics)
Autosomal recessive polycystic kidney disease is a renal development anomaly characterized by cystic transformation in renal parenchyma. ARPKD is more common in children. We present the case of a premature newborn, female, 36-37 weeks gestation, small for gestational age (SGA) originating from a completely unmonitored pregnancy, diagnosed upon admission to the clinic with unilateral multicystic dysplastic kidney. The condition complicated by a urinary tract infection with E. coli. This newborn displayed no clinical symptoms, was carefully monitored during hospitalization, and received antibiotic treatment. Antenatal ultrasound screening can aid in the early diagnosis of congenital anomalies and determining the appropriate course of action.